2021
DOI: 10.1111/jcmm.17000
|View full text |Cite
|
Sign up to set email alerts
|

Down‐regulated LINC00115 inhibits prostate cancer cell proliferation and invasion via targeting miR‐212‐5p/FZD5/Wnt/β‐catenin axis

Abstract: Prostate cancer is the second most frequent malignancy in men worldwide, and its incidence is increasing. Therefore, it is urgently required to clarify the underlying mechanisms of prostate cancer. Although the long non‐coding RNA LINC00115 was identified as an oncogene in several cancers, the expression and function of LINC00115 in prostate cancer have not been explored. Our results showed that LINC00115 was significantly up‐regulated in prostate cancer tissues, which was significantly associated with a poor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…We found that GDPD4-2, AC144450.1, LINC01513, AC004009.2, AL096869.1, AP005210.1, and BX119924.1 were significantly underexpressed in PCa. LINC01513 was underexpressed in nasopharyngeal carcinoma (Wang J. et al, 2021). However, AC144450.1 has been found to be highly expressed in the breast tissue relative to the adjacent tissue (Hassani et al, 2021).…”
Section: Discussionmentioning
confidence: 95%
“…We found that GDPD4-2, AC144450.1, LINC01513, AC004009.2, AL096869.1, AP005210.1, and BX119924.1 were significantly underexpressed in PCa. LINC01513 was underexpressed in nasopharyngeal carcinoma (Wang J. et al, 2021). However, AC144450.1 has been found to be highly expressed in the breast tissue relative to the adjacent tissue (Hassani et al, 2021).…”
Section: Discussionmentioning
confidence: 95%
“…In cell lines increased expression of CARD8-AS1 reduces cell viability and affects cell migration and invasion abilities in lung adenocarcinoma cells by targeting miR-650. Accumulating evidence demonstrates the functional and clinical roles of lncRNAs involved in tumor progression [19][20][21]. For instance, lincRNA OIN1 is oncogenic in ovarian cancer and a potential molecular target for its treatment [22].…”
Section: Discussionmentioning
confidence: 99%
“…Transfected cells at the logarithmic growth stage were washed with a precooled PBS buffer, and 100 μ l of precooled RIPA (containing 1 μ L PMSF) was added. The cells were lysed on ice for 30 min, and the supernatant was collected by centrifugation and quantified by using the BCA protein quantification kit as described in the literature [ 17 ]. Samples were added to the gel wells at 70 μ g per lane and electrophoresed at a constant pressure of a 40 V (concentrate)/100 V (separator) until bromophenol reached the edge of the gel.…”
Section: Methodsmentioning
confidence: 99%